Metropolregionen: Impulsgeber für Strukturwandel und wirtschaftliche Entwicklung - Silvia Stiller; Isabel Sünner (Wirtschaftsdienst, 2013)
Städte und ihr Umland bilden vielerorts in Deutschland dynamische Wachstumsregionen. Aufgrund ihrer Bevölkerungsgröße und der hohen Zahl an Arbeitsplätzen gehen von diesen Metropolregionen Impulse für die wirtschaftliche Entwicklung Deutschlands insgesamt aus. Dabei konzentrieren sich die Dienstleistungsunternehmen in den Städten und die gewerbliche Wirtschaft in den anderen Teilen der Metropolregionen. Wichtig für die Zukunft ist die Stärkung der überregionalen Metropolfunktionen sowie der Ausbau der Verkehrsinfrastruktur zwischen Metropole und Umland. – – Urban centres and their surroundings often act as highly dynamic economic areas. Due to continuing urban migration, population growth as well as their heightened potential for employment, they have significant impact on Germany's overall economic performance. Cities benefit from their neighbouring regions via a division of labour based on functional and spatial comparative advantages. Jobs in the service sector are concentrated in the city, while surrounding regions show a relatively high specialisation in the industrial sector. The economic development of metropolitan regions can be fostered particularly by improving supra-regional metropolitan functions related to education and to research and development. Moreover, the improvement of the intra-regional infrastructure also contributes to the economic strength of the whole metropolitan area.
Keywords: R11; R12; 330; Ballungsraum; Standortfaktor; Regionaler Strukturwandel; Regionale Entwicklung; Deutschland